Correction: Visual organophosphate vapor sensing by dibenzylidine derivatives exhibiting intramolecular charge transfer and aggregation induced emission. Issue 23 (1st June 2022) - Manikandan, Rajendran; Shauloff, Nitzan; Nandi, Ashim; Baranov, Mark; Pevzner, Alexander; Marx, Sharon; Jelinek, Raz
Abstract : Correction for 'Visual organophosphate vapor sensing by dibenzylidine derivatives exhibiting intramolecular charge transfer and aggregation induced emission' by Rajendran Manikandan et al., J. Mater. Chem. C, 2022, 10, 5458–5465, DOI: ; https://doi.org/10.1039/D1TC05566F .